2008
DOI: 10.1091/mbc.e08-05-0455
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast LATS/Ndr Kinase Cbk1 Regulates Growth via Golgi-dependent Glycosylation and Secretion

Abstract: Saccharomyces cerevisiae Cbk1 is a LATS/Ndr protein kinase and a downstream component of the regulation of Ace2 and morphogenesis (RAM) signaling network. Cbk1 and the RAM network are required for cellular morphogenesis, cell separation, and maintenance of cell integrity. Here, we examine the phenotypes of conditional cbk1 mutants to determine the essential function of Cbk1. Cbk1 inhibition severely disrupts growth and protein secretion, and triggers the Swe1-dependent morphogenesis checkpoint. Cbk1 inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 107 publications
(226 reference statements)
1
64
0
3
Order By: Relevance
“…Wee1 is a target of Ukc1) or indirect effect. It is interesting to note that previous research done in S. cerevisiae indicated that loss of Cbk1 function prevented bud emergence and caused a G2 arrest, which was the consequence of the activation of the morphogenesis checkpoint (Kurischko et al, 2008). In budding yeast, morphogenesis checkpoint operates by phosphorylation of Tyr15 of Cdc28 by Swe1, the S. cerevisiae homolog of Wee1 (Lew, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wee1 is a target of Ukc1) or indirect effect. It is interesting to note that previous research done in S. cerevisiae indicated that loss of Cbk1 function prevented bud emergence and caused a G2 arrest, which was the consequence of the activation of the morphogenesis checkpoint (Kurischko et al, 2008). In budding yeast, morphogenesis checkpoint operates by phosphorylation of Tyr15 of Cdc28 by Swe1, the S. cerevisiae homolog of Wee1 (Lew, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In budding yeast, morphogenesis checkpoint operates by phosphorylation of Tyr15 of Cdc28 by Swe1, the S. cerevisiae homolog of Wee1 (Lew, 2003). In fact, the G2 arrest consequence of Cbk1 inhibition in S. cerevisiae was prevented by deletion of Swe1 (Kurischko et al, 2008). One interesting possibility is that defects in MOR pathway in U. maydis triggers some sort of morphogenesis checkpoint and as a consequence the cell cycle is affected as it happens in S. cerevisiae.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Kurischko et al (2008) have shown that Cbk1p and the -2, 3-4, 5-7, 8-12, 13-15, 16-20, 21-29, and .29 cells. The mean and standard deviation between the three experiments are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, wts-1 might phosphorylate target proteins that regulate cellular integrity. Interestingly, Cbk1 in budding yeasts binds and phosphorylates Sec2, a guanyl-nucleotide exchange factor (GEF), which is involved in polarized growth and secretion in yeast (Kurischko et al, 2008). There are many GEF homologs in C. elegans, and it would be of interest to examine whether any of these can be phosphorylated by WTS-1.…”
Section: Research Articlementioning
confidence: 99%